2020
DOI: 10.1101/2020.07.30.229617
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards understanding how we pay attention in naturalistic visual search settings

Abstract: Traditional research on attentional control has largely focused on single senses and the importance of one s behavioural goals in controlling attentional selection, thus limiting its generalizability to real-world contexts. These contexts are both inherently multisensory and contain regularities that also contribute to attentional control. To get a better understanding of how attention is controlled in the real world, we investigated how visual attentional capture was impacted by top-down goals (indexed by tas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 140 publications
2
8
0
Order By: Relevance
“…Despite adapting the original paradigm to children and adding an EEG measurement, also adults in our study showed the behavioural MSE effect. This corroborates the particular salience of multisensory distractors ( Santangelo and Spence, 2007 ; Talsma et al, 2010 ; van der Burg et al, 2011 ; Matusz and Eimer, 2011 ; Matusz et al, 2015 , 2019a ; Turoman et al, 2020a ), further supported by evidence that multisensory integration can occur at stages of brain processing preceding those influenced by top-down processes ( Giard and Peronnet, 1999 ; Cappe et al, 2010 ; reviewed in Talsma et al, 2010 ; De Meo et al, 2015 ; Murray et al, 2016 ; ten Oever et al, 2016 ). Surprisingly, none of the children groups showed MSE in behaviour, even though children supposedly have weaker attentional control than adults ( Bunge et al, 2002 ; Hwang et al, 2010 ) and so should be theoretically more sensitive to more salient distractors.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Despite adapting the original paradigm to children and adding an EEG measurement, also adults in our study showed the behavioural MSE effect. This corroborates the particular salience of multisensory distractors ( Santangelo and Spence, 2007 ; Talsma et al, 2010 ; van der Burg et al, 2011 ; Matusz and Eimer, 2011 ; Matusz et al, 2015 , 2019a ; Turoman et al, 2020a ), further supported by evidence that multisensory integration can occur at stages of brain processing preceding those influenced by top-down processes ( Giard and Peronnet, 1999 ; Cappe et al, 2010 ; reviewed in Talsma et al, 2010 ; De Meo et al, 2015 ; Murray et al, 2016 ; ten Oever et al, 2016 ). Surprisingly, none of the children groups showed MSE in behaviour, even though children supposedly have weaker attentional control than adults ( Bunge et al, 2002 ; Hwang et al, 2010 ) and so should be theoretically more sensitive to more salient distractors.…”
Section: Discussionsupporting
confidence: 74%
“…paying attention to fast-disappearing targets of a particular colour embedded in an array of similar coloured shapes) and cross-modal audiovisual interactions within task-irrelevant objects that may be less automated in children. Finally, the behavioural MSE itself is not large even in adults, ranging between 5 and 10 ms (see also Matusz and Eimer, 2011 ; Turoman et al, 2020a ). Notwithstanding, using EN analyses we revealed the sensitivity of children’s brains to the multisensory nature of distractors and the recruitment of adult-like neuro-cognitive mechanisms for this purpose, from 8 years onwards.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Despite adapting the original paradigm to children and adding an EEG measurement, also adults in our study showed the behavioural MSE effect. This corroborates the particular salience of multisensory distractors (Santangelo & Spence 2007; Talsma et al 2010; van der Burg et al 2011; Matusz & Eimer 2011; Matusz et al 2015; 2019a; Turoman et al 2020a), further supported by evidence that multisensory integration can occur at stages of brain processing preceding those influenced by top-down processes (Giard & Peronnet 1999; Cappe et al 2010; reviewed in Talsma et al 2010; De Meo et al 2015; Murray et al 2016; ten Oever et al 2016). Surprisingly, none of the children groups showed MSE in behaviour, even though children supposedly have weaker attentional control than adults (Bunge et al 2002; Hwang et al 2010) and so should be theoretically more sensitive to more salient distractors.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, classical N2pc analyses take into account much less EEG data than EN analyses, which suggests that EN analyses may detect effects that the canonical N2pc analyses may miss. In combination with rigorous paradigms and analyses of well-understood EEG correlates of cognitive processes, an EN approach offers a powerful tool to distinguishing between different accounts of cognitive processes, including multisensory attentional control (Matusz et al 2019b; Turoman et al 2020a).…”
Section: Introductionmentioning
confidence: 99%